Impact of Direct Cash Assistance (BLT) on Community Welfare in Pa'rappunganta Village, North Polongbangkeng District, Takalar Regency - Asdar; Nur Alfilahi Tahir; Andi Jam'an (Perpustakaan dan Penerbitan Unismuh Makassar, 2025)
This study examines the impact of Direct Cash Assistance (Bantuan Langsung Tunai/BLT) on community welfare in Pa’rappunganta Village, Polongbangkeng Utara District, Takalar Regency, Indonesia. Despite the widespread implementation of BLT as a social protection instrument, empirical evidence on its effectiveness in improving long-term welfare at the village level remains limited. This research aims to analyze the extent to which BLT contributes to community welfare and to identify its practical limitations. A qualitative research approach was employed, using primary and secondary data collected through in-depth interviews, direct observation, and document analysis. Informants consisted of BLT recipients, village officials, and community representatives selected purposively based on their involvement in the program. Data were analyzed using thematic analysis with triangulation to ensure validity and reliability. The findings reveal that BLT provides short-term financial relief and helps households meet basic consumption needs, particularly during periods of economic vulnerability. However, the assistance does not significantly improve long-term welfare, income stability, or quality of life, nor does it effectively reduce poverty levels. This limitation is mainly due to the temporary nature of the program and the absence of complementary empowerment or income-generating initiatives. The study contributes to the literature on social assistance by highlighting the gap between short-term aid effectiveness and sustainable welfare improvement. Policy implications suggest that BLT should be integrated with productive economic programs to achieve more sustainable social welfare outcomes.